AKSS16-LIV01: An Antioxidant and Immunity-Boosting Multiherbal Formulation for Alcoholic Liver Dysfunction in Experimental Animal Model - Soumendra Darbar; Srimoyee Saha; Kausikisankar Pramanik; Atiskumar Chattopadhyay (Recent Developments in Chemistry and Biochemistry Research Vol. 5, 2024)
High rates of alcohol intake are frequently the cause of liver complications. The majority of alcohol-drinking citizens in industrialized and developing nations suffer from cirrhosis, fatty liver, liver fibrosis, and even hepatocellular cancer, among other liver issues. Creating symptomatic, safe medication to go through this is a new global problem. The primary goal of the research is to provide a symptomatic, safe medicine to lessen liver damage caused by ethanol. We created a multi-herbal formulation (AKSS-16-LIV01), which may be helpful in liver complications. In this investigation, we try to reduce liver damage from a variety of toxicants. Swiss albino mice were split up into seven groups, and each group was subjected to ethanol-induced injury for several weeks before our herbal preparation was used to investigate a healing response. The groups include the normal control group (Group-I), the group treated with 50% v/v ethanol (Group-II), the groups pre-treated with AKSS16-LIV01 at a low dose of 100 mg/kg/day (Group-III), the group pre-treated with AKSS16-LIV01 at a middle dose of 200 mg/kg/day (Group-IV), the group pre-treated with AKSS16-LIV01 at a high dose of 400 mg/kg/day (Group-V), the group pre-treated with Sylimarin at 100 mg/kg/day (Group-VI), and the only group treated with AKSS16-LIV01 (400 mg/kg/day) (Group-VII).In the mice given ethanol, the results showed a marked increase in a number of biochemical parameters, lipid profile parameters, lipid peroxidation, nitric oxide (NO) concentration, nitric oxide synthase level, and pro-inflammatory cytokines, such as tumour necrosis factor (TNF-\(α\)) and transforming growth factor (TGF-\(β\)1). However, ethanol significantly decreased the levels of tissue antioxidant enzyme activity (SOD, CAT, GSH, and GPx), serum total protein, total albumin, albumin globulin ratio, and tissue total antioxidant enzyme activity. The formulation (AKSS16-LIV01) was applied therapeutically at a dose that determined its effectiveness in suppressing all relevant parameters mentioned above, while also shielding the liver from ethanol-induced fibrogenesis. In addition to this gross morphology of the liver, the hepato-protective impact of the formulation in comparison to the usual medication Sylimarin was clearly supported by H&E liver histology and Masson trichrome and serius red analysis of the liver sections. According to the study’s findings, a multi-herbal formulation that was designed (AKSS16-LIV01) and given at a dose of 400 mg/kg/day produced the best possible response to lessen ethanol intoxication. The results unmistakably show that AKSS16-LIV01 may be a safe and non-toxic drug that shields the liver from oxidative damage caused by ethanol and keeps levels of pro-inflammatory cytokines stable over time.